NADUŻYCIE PRAWA W DZIEDZINIE PRZEDAWNIENIA W KONTEKŚCIE PRZEDWOJENNYCH PAPIERÓW SKARBOWYCH - Włodarczyk, Marcin (Zeszyty Prawnicze, 2016)
The Abuse of Rights in the Area of Limitation in the Context of Pre-war Treasury Securities Summary Treasury securities of 1939 create a major, embarrassing problem for the Polish financial market. Longstanding commitment may in fact expose the Polish state on the giant compensation. This article presents the pre-war fate of Treasury securities, and also reflects the position of the Ministry of Finance and Treasury for the benefit of the institutions of its limitation. It must be always remembered the reasons for the introduction to the legal system the institution as a means of eliminating long-standing contractual relations between market operators. That was not the case in the context of pre-war Treasury securities. War and fifty years of communism made it impossible to unfettered implementation of the commitments under the pre-war bonds. This article aims to show the need for a statutory resolution of pre-war securities by specific laws that are created for the purpose of restitution in the Polish legal system.